Materialism and Religious Perspective: An Analysis of Karl Marx's Thought - Juwaini, Juwaini; Yasin, Taslim HM; Safira, Cut Siska (Prodi Studi Agama-Agama, 2024)
Karl Marx was a philosopher and social observer, whose intelligence and brilliant thinking earned him a position as a political leader among the proletarian class of his time. For Marx, the essence of humanity lies in labor, and religion is a product and expression of the interests of the oppressed lower classes. Living in Europe during the industrial age, Marx's thoughts differed significantly from those of other philosophers of his time. This text examines Marx's thoughts on Materialism, religious beliefs, and Marxist Economics. Research findings indicate that Historical Materialism proposed by Marx is a useful term for providing the basic assumptions of his theory. The emphasis in his work